Analysis of Road Surfacing Using the Pavement Condition Index (PCI) and Surface Distress Index (SDI) - Vikram, Dio; Erizal; Apriadi (Departemen Teknik Sipil dan Lingkungan IPB, 2025)
A roadway is an important infrastructure for the smooth flow of the economy. High traffic volume and frequent use decrease the quality of the road and affect traffic comfort. It is important to maintain roads regularly, effectively, and efficiently. The PCI and SDI methods are effective ways to evaluate road damage advantages reflecting the actual condition of the damage. This study aim to analyze the condition of the road and comparing the maintenance cost based on assessment result from this two methods. The location conducted on connecting road at Cilubang Mekar Road in the city of Bogor. The survey covered damage such as alligator cracking, edge cracking, shoulder settlement, patching, potholes, and deterioration. The PCI value was 66.92, indicating a moderate rating, and the SDI value was 35, indicating a good rating. The recommended methods for handling the severity using the City Road Maintenance System Guidelines No. 02/P/BM/2025 are P2 (paving), P5 (patching), P6 (leveling), and U3 (regrading). An overlay of 4 cm is also recommended. The estimated cost of repairing the Cilubang Mekar road is Rp 50,021,000 based on the PCI method and Rp 30,336,000 based on the SDI method. However, since patching and potholes significantly impact the road, it is sufficient to use the SDI method for repairs.